Pengaruh penambahan limestone terhadap kuat tekan semen Portland komposit - Irfan Purnawan; Andi Prabowo (Jurnal Rekayasa Proses, 2017)
Cement is the main component of construction that makes it a significant commodity. Portland Composite Cement (PCC) is one of new cement variants that has similar characteristic to Portland Cement, but with better quality, more environmentally friendly and cheaper in price. The objective of this research is to understand the influence of limestone to the compressive strength of the cement and to determine the percentage of added limestone that gives maximum compressive strength to PPC. The limestone varies added to the cement are 0, 5, 10, 15, 20 and 25%. The impact of added limestone can be studied from several tests such as fineness test, residue test, chemical composition test and cement compressive strength. The result shows that the higher percentage of limestone added to the cement, the higher the result for residue test and fineness test, but lower result for compressive strength. The highest compressive strength obtained is at 2 days age while the best composition of the blended cement is 77% clinker, 15% limestone, 3% gypsum and 5% blast furnace slag.